The Effect of Additional Cetane Booster and Water Methanol Injection (WMI) on Torque and Power in Diesel Engines - Rahmat, Rahmat; Hadi, Samsul (Evrimata: Journal of Mechanical Engineering, 2025)
The development of technology in motor vehicles, especially in improving engine performance, is increasingly developing. One of the technological developments is water methanol injection or often abbreviated as WMI, which is injecting water with methanol into the engine combustion chamber through the intake manifold. Methanol can be used by mixing it with fuel or used alone (pure methanol) and is able to produce more heat than fuel. High-quality fuel certainly comes with a high price tag. For that reason, cetane booster is one of the innovations to improve fuel quality. The purpose of this study was to determine the effect of Water Methanol Injection on power and torque in Diesel Engines. In addition, this study also analyzed the interaction of the WMI mixture with the addition of cetane booster. Testing was conducted using a four-wheeled motor vehicle with an Elf Long 2771 CC engine type, using Solar B30 fuel, with three variations of WMI percentage, namely 10%, 30%, and 50%, without cetane booster and with booster. Testing was carried out at 1500 to 2500 rpm with an increase of 500 rpm using a dyno test tool. Data processing was performed using Two-Way ANOVA, commonly known as 2-way ANOVA. The tests conducted were power and torque tests. The study results showed maximum results at 2500 rpm rotation power at a WMI percentage of 30% with the addition of 150ml booster, reaching 77.19 Hp and a torque of 234.43 Nm. Therefore, it can be concluded that the use of a mixture of methanol and water has increased power and torque, although not significantly, while the addition of a 150ml booster has a major influence on the results of the power and torque tests.